Targeting phosphodiesterase-5 by vardenafil improves vascular graft function - Veres, Gábor; Hagenhoff, Meike; Schmidt, Harald; Radovits, Tamás; Loganathan, Sivakkanan; Bai, Yang; Korkmaz-İçöz, Sevil; Brlecic, Paige; Sayour, Alex Ali; Karck, Matthias; Szabó, Gábor (European journal of vascular and endovascular surgery, 2018)
Ischaemia reperfusion (IR) injury occurs during vascular graft harvesting and implantation during vascular/cardiac surgery. Elevated intracellular cyclic guanosine monophosphate (cGMP) levels contribute to an effective endothelial protection in different pathophysiological conditions. The hypothesis that the phosphodiesterase-5 inhibitor vardenafil would protect vascular grafts against IR injury by upregulating the nitric oxide-cGMP pathway in the vessel wall of the bypass graft was investigated.
Gesehen am 09.04.2020